2008
DOI: 10.1134/s0006297908070080
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Mullerian inhibiting substance receptors in various human cancer cell lines

Abstract: Recombinant human MIS (rhMIS) produced in transfected Chinese hamster ovary cells has been purified by immunoaffinity chromatography. In the absence of reducing agents, 140 kD homodimer and several oligomers with molecular masses from 280 to 1000 kD are present. Homodimer, tetramer, and higher-molecular-weight rhMIS fractions reduced survival of tumor cells. For these experiments, FITC-labeled rhMIS was used for binding and endocytosis studies by flow cytometry. Flow cytometry performed on MIS-sensitive cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…As COV434-AMHRII cells, used as positive control, most of the cells expressing AMHRII showed diffuse, predominantly cytoplasmic immunostaining, with a moderate to strong intensity and constant membranous staining. This was in accordance with previous observations suggesting a high pool of intracellular AMHRII receptors in cancer cells [43] and regulation of AMHRII expression by intracellular retention [32]. Due to this distribution, a GHs was established, considering both cytoplasmic (Cy) and membranous (Mb) AMHRII expression: GHs = (Mb Intensity × Mb Frequency) + (Cy Intensity × Cy Frequency).…”
Section: Immunohistochemistrysupporting
confidence: 91%
“…As COV434-AMHRII cells, used as positive control, most of the cells expressing AMHRII showed diffuse, predominantly cytoplasmic immunostaining, with a moderate to strong intensity and constant membranous staining. This was in accordance with previous observations suggesting a high pool of intracellular AMHRII receptors in cancer cells [43] and regulation of AMHRII expression by intracellular retention [32]. Due to this distribution, a GHs was established, considering both cytoplasmic (Cy) and membranous (Mb) AMHRII expression: GHs = (Mb Intensity × Mb Frequency) + (Cy Intensity × Cy Frequency).…”
Section: Immunohistochemistrysupporting
confidence: 91%
“…To consider other therapeutic agents that can target SP cells and NSP cells, we turned to extracellularly active receptor mediated agents and tested the effects of MIS, as mouse ovarian surface epithelium expresses MIS RII receptors (21,29,30), as do human ovarian cancer cell lines and primary ovarian cancer ascites cells (20). We found that MIS and its small molecule MISRII receptordependent agonist, SP600125 (23), significantly decreased SP cell percentages in OVCAR-5, IGROV-1, and SKOV-3.…”
Section: Discussionmentioning
confidence: 99%
“…AMHR2 is expressed in the prostate gland, prostate cancer cell lines, and human prostate adenocarcinomas [9]. AMH has been shown to inhibit the growth of human prostate cancer cell lines [89]. Additionally, because AMH suppresses testicular testosterone production and regulates androgen-induced gene expression and growth in prostate cancer cells, it may act via several synergistic mechanisms in the treatment of prostate cancer [90].…”
Section: Prostate Cancermentioning
confidence: 99%